INTEGRATION OF TRADITIONAL AND INNOVATIVE TEACHING METHODS: THE WAY TO EFFECTIVE EDUCATION - Ismanova Maluda Mamadaliyevna,; Zhabborova Muslima Tokhirovna, (PEDAGOGS, 2025)
Abstract. The article examines the problem of integrating traditional and modern methods in educational practice. The main difficulties that arise when trying to combine classical pedagogical approaches with innovative forms and digital technologies are analyzed. Particular attention is paid to the psychological and pedagogical aspects of adaptation of participants in the educational process to new conditions. Possible ways to overcome the identified difficulties are presented and prospects for further development of an integrative approach in education are outlined.